Problematika Verifikasi Partai Politik Peserta Pemilu: Urgensi Perubahan dan Konsep Perbaikan Regulasi - Atmaja Wijaya; Rakha Imadi Fadli (Fakultas Hukum, Universitas Warmadewa, 2024)
This research examines problems related to the verification process of political parties participating in the 2024 election, namely where there are differences in the verification process given to parliamentary and non-parliamentary political parties or new political parties. Where the parliamentary party does not go through a factual verification process, only through administrative verification. Meanwhile, new or non-parliamentary political parties must go through an administrative verification process and also factual verification. The aim of this research is to explain the problems in the verification process both in terms of normative and impellative rules in the field. This research is included in the category of normative legal research, which reviews and examines statutory regulations. The approach used is a statutory approach, which is used to examine the problems of verifying political parties participating in elections. The findings and results in this research are important for improving regulations related to the verification of political parties participating in elections, by including that there are no differences in the verification process for political parties to become election participants, so that there is no discrimination and for the sake of justice and legal certainty, the regulations can be improved. regulated at the same level as the Election Law which is based on the Election Law.